Reflection of the concept "suyekshi" in the work of D. Issabekov and its reproduction in translations into the Russian, English languages (Eurasian Journal of Philology Science and Education, 2024)
The article is devoted to the study of the reflection of D. Issabekov's individual author's concept "suyekshi" in his work of the same title and the difficulties of reproduction in translations into Russian and English, taking into account the national and cultural characteristics of this concept. Since all three languages have their own linguistic features, it can be seen that there are differences in the historical causes of the mentality, worldview, and development of general concept. In the article, the authors demonstrate a cultural approach to the concept and prove that linguistic and cultural difficulties often arise in the process of translating the concept "suyekshi". The authors adhere to the opinion about the concept as having a meaning-generating function. The study revealed that the volume and content of the concept "suyekshi" depends on the individual cognitive experience of the author and are largely determined by the living conditions and culture of the people. These differences in the meaning of the word "suyekshi" most clearly appear in translation, when it is necessary to adequately transfer this concept in the Kazakh language by means of the Russian and English languages. As a result, article determined with the help of a comparative method, national and cultural characteristics, and identified translation strategies.Key words: author's concept, linguistic and cultural difficulties, adequate translation, translation transformations.